The Analysis of Linguistics Features of Ecovacs Vacuum Robot Deebot Ozmo 920 Manual Book: A Procedure Text - Ellyawati, Hetty Catur; Yogatama, Adiprana; Laksmi Tatas, Hernofika (Universitas PGRI Semarang, 2023)
Manual book is a guidebook made to convey information related to the product purchased by consumers. This information is usually detailed regarding warranty information, safety instructions, installation instructions, problem identification, setup instructions, general specifications about the product and maintenance and troubleshooting instructions. The objective of this qualitative research was to analyze schematic structure in a procedure text of Ecovacs Vacuum Robot Deebot Ozmo 920 manual book, especially in Important safety instruction text. There are 44 utterances in text of Important Safety Instruction that are picked up randomly as some samples of analysis. Before they are analyzed, the utterances were grouped with the same linguistics categories, those are simple present tense, imperative sentence, declarative sentence, conjunction, and material process. In material process, there are two categories to discuss, they are passive voice and active voice. Then using schematic structure form, the data were analyzed one by one. The findings of this study show that the language used in Important safety instruction text in manual book is concise, as evidenced by the low percentage of conjunctions (4%). Another is the language used in the text of the Important safety instruction text is effective and direct, as shown by the high percentages of declarative (20%) and imperative sentences (27%), this reduces the possibility of misunderstandings or misinterpretations moreover, the pattern makes the information being conveyed directly easy to understand. Moreover, the study only discusses linguistic features to explain how to describe the use of language in a straightforward procedural text